The Relationship Between Social Media Exposure with Sexual Content and Acceleration of Menarche Age in the Area of Lowokwaru District, Malang City: HUBUNGAN ANTARA PAPARAN SOSIAL MEDIA DENGAN KONTEN SEKSUAL TERHADAP PERCEPATAN USIA MENARCHE DI WILAYAH KECAMATAN LOWOKWARU, KOTA MALANG - Khafidhiyah Nur Insaniyah; Evi Dwi Prastiwi (STIKes Maharani Malang, 2025)
In the last decade, the age of menarche has shifted to a younger age, influenced by several factors, including internal and external ones. One external factor that can influence the age of menarche is exposure to mass media messages intended for adults. Moreover, current media often contains sexual themes, resulting in messages with sexual content. This can pique curiosity about sex, which in turn may accelerate the maturation process in adolescents. The objective of this study was to assess the relationship between adolescent exposure to adult-oriented mass media messages and the acceleration of menarcheal age. A correlational analytic design was used to determine the relationship between exposure to adult-oriented mass media messages and the acceleration of menarcheal age at SDN Kesatrian I-Malang. The study population consisted of 41 female students in the 4th, 5th, and 6th grades at SDN Kesatrian I Malang in 2012 who had already experienced menarche. The sample included all 41 students, utilizing a total sampling technique. Data were analyzed using the Fisher's Exact Test with a significance level of α=0.05. The results showed a p-value of 0.028. As p<α (0.028 < 0.05), the null hypothesis (H0) was rejected. It can be concluded that there is a significant relationship between exposure to adult-oriented mass media messages and the acceleration of menarcheal age at SDN Kesatrian I-Malang. This scientific paper is expected to be beneficial for all readers. The researcher recommends that future studies investigate other factors influencing the age of menarche in female adolescents. Keyword: Social Media, Menarche, Sexual Content